Long-term comparison of climatological variables used for agricultural land appraisement - STŘEDOVÁ, Hana; STŘEDA, Tomáš; ROŽNOVSKÝ, Jaroslav (Contributions to Geophysics and Geodesy, 2013)
Official price of farmland in the Czech Republic is based on land value in different soil and climatic conditions. The paper compares relevant climatic and agroclimatic characteristics used for land appraisement. Characteristics defined in climatic region of estimated pedological ecological unit system for two fifty years period 1901–1950 and 1961–2010 were evaluated. Area of interest includes 53 points distributed within nine broad areas of the Czech Republic. It is evident that the development of climate has an enormous impact on soil fertility. Difference of station average values of air temperature of both fifty years vary from −0.5 to 1.1◦ C (mean difference is 0.3◦C) in the case of vegetation period. The shift of precipitation is not so evident as in the case of temperature. The long term change in precipitation distribution within a year is documented by a different shift of annual, vegetation period and non-vegetation period values. Moisture certainty in vegetation period decreases in all cases of broad areas (except one region). All 50year averages of investigated parameters had been changed in 1961–2010 compared to the mean of 1901–1950. This should be taken into account when fixing the official price. Climatic region parameters should be replaced by a more complex “agroclimatological characteristic”, which take into account also the basic pedological and plant characteristics, for example the available water holding capacity.